Identyfikacja gatunku mowy pochwały w oparciu o strategię reaktywnego gatunku mowy (SRGM) - Wartecka, Anna (Investigationes Linguisticae, 2019)
The main purpose of this article is to explain the procedure of identifying the utterances of praise using the Reactive Speech Genre Strategy (RSGS). The RSGS is one of the steps of a wider strategy dedicated to identification of “Praise” speech genre. In the article are described 5 stages of RSGS, which include considerations over: the initiative nature of “Praise” speech genre; the role of the reactive nature of “Gratitude” speech genre in identifying the “Praise” speech genre; the analysis of selected speech genres associated with “Praise” and “Gratitude”. The linguistic corpus consists of selected utterances of positive assessment taken from the Polish version of a television talent show “Mam talent!”.